Investigation of Traffic Characteristics and Arrival Patterns at Pertashop in Suburban Area of Semarang City - Mutia Ayu Lestari; Ferry Hermawan; Alfa Narendra (Jurnal Sistem Informasi Bisnis, 2025)
Pertashop, developed by PT. Pertamina, is a small-scale gas station business designed to meet the fuel needs of vehicles in suburban areas while maintaining fuel quality. Variations in land use functions can lead to different travel attractions, leading to varied arrival patterns and potential traffic flow disruptions, thus impacting road quality around Pertashop locations. This study seeks to investigate the traffic characteristics and arrival patterns at small-scale gas stations such as Pertashop, providing a basis for development planning and optimizing services in the suburban areas of Semarang City. Using qualitative and quantitative descriptive research methods, the study analyzes the relationship between land use factors and traffic characteristics on Pertashop vehicle service patterns. The findings indicate that the traffic flow around Pertashop follows the Underwood model, demonstrating that vehicles entering Pertashop hinder the traffic flow on surrounding roads.